The influence of subtalar axis orientation on the foot posture of older adults in a closed kinetic chain - Liliana Marta Mirra Araújo Avidos; José Carlos Gomez Diz; Fernanda Nunes Ribeiro; Maria Elena Padin-Iruegas; José Maia Neves (Brazilian Society of Geriatrics and Gerontology, 2022)
Objectives: This study compared the influence of subtalar axis position on foot behavior in a closed kinetic chain in older and younger adults. Methods: The sample included 50 older adults and a control group of 50 younger adults. The variables were initially analyzed for both feet together, and were later analyzed separately, comparing each foot (right and left) between groups. Range of motion was assessed by validated goniometric procedures: the position of subtalar axis was evaluated by the palpation technique, while the Foot Posture Index was used to assess behavior in a closed kinetic chain. Student's t-test / Mann-Whitney test compared the main variables according to sample distribution, while Student's t-test / Wilcoxon test was used for paired samples. A standardized Haberman residuals test was also used to determine the connection between the position of subtalar joint axis and the Foot Posture Index. Results: Data from the right and left feet were similar for all variables. The older group had reduced mobility in the ankle and first metatarsophalangeal joint (5.42º [SD (Standard Deviation), 4.49] and 76.12º [SD, 19.24], respectively) with statistically significant values, (p <0.001), as measured by the Mann-Whitney test for the ankle joint and the t-Sutdent test for the first metatarsophalangeal joint, while the younger group had normal values (11.46º [SD, 6.49] and 97.17º [SD, 13.65], respectively)(p < 0.001). The difference in subtalar axis position was not significant (p = 0.788), with more internal deviations in both groups. There was a significant difference in Foot Posture Index (p = 0.006, by applying the chi-square test), with the normal position more prevalent in the older group and the prone position more prevalent in the younger group. Conclusions: Regarding internal deviations in the subtalar joint axis, the older group had a higher frequency of feet in the normal position, while the younger group had a higher frequency of feet in the prone position which, in this case, agrees with the rotational balance theory. For the normal axis position, a higher frequency of normal position was found in both groups. Regarding external deviations of the subtalar joint axis, neither group followed the pattern expected in rotational balance theory. The most consistent connection in the older group was between external axis position and supine foot position, whereas in the younger group it was between normal axis position and normal foot position.